COVID-19 vaccine confidence among parents of racially diverse children aged 0–12 years old in Canada: The role of major experience of racial discrimination, health literacy, and conspiracy beliefs - Seyed Mohammad Mahdi Moshirian Farahi; Rose Darly Dalexis; Idrissa Beogo; Léa Gakima; Jude Mary Cénat (Human Vaccines & Immunotherapeutics)
The success of COVID-19 vaccination is linked to trust, hesitancy, and confidence. Racial discrimination impacts vaccine hesitancy and trust, particularly in racialized groups. This study investigates factors influencing COVID-19 vaccine confidence among Canadian parents from different racial groups, addressing a gap in existing research. Data were collected in 2023 (October to November) included 2,528 parents of children aged 0–12. Findings showed significant mean differences between racial groups, F (7, 2520) = 9.92, p < .001, with Arabs presented lower means of confidence (M = 30.26, SD = 9.39) compared to Asian (M = 35.71, SD = 8.14), Black (M = 33.23, SD = 9.50), and Indigenous parents (M = 35.07, SD = 9.45). Multiple linear regression among White participants showed that conspiracy beliefs were negatively associated with COVID-19 vaccine confidence (β = -.60, p < .001), whereas health literacy was positively associated with COVID-19 vaccine confidence (β = .09, p < .001). Results among racialized groups showed that conspiracy beliefs (β = -.23, p < .001) and racial discrimination (β = -.05, p = .049) were negatively associated with COVID-19 vaccine confidence, while health literacy was positively associated with COVID-19 vaccine confidence (β = .31, p < .001). This study highlights the complex factors influencing COVID-19 vaccine confidence among Canadian parents from racialized groups, suggesting that racial discrimination and conspiracy beliefs significantly reduce vaccine confidence, while health literacy plays a crucial role in increasing confidence. These results underscore the importance of addressing misinformation and systemic barriers to trust in vaccination efforts.